The Role Of Customer Satisfaction As A Mediation Of The Influence Of Celebrity Endorsement And Brand Image On Customer Loyalty Of Kopi Kapal Api In West Bandung - Henty Emiliawati; V. Santi Paramita (UNIVED Press, 2025)
This research aims to analyze the influence of celebrity endorsement and brand image on customer satisfaction which is mediated by the satisfaction of Kapal Api coffee customers in West Bandung. The type of research used in this research is quantitative. The population in this study were consumers who made repeated purchases of Kapal Api coffee. Meanwhile, the number of samples taken was 100 respondents using purposive sampling technique. This research uses analytical tools in the form of validity tests, reliability tests, classical assumption tests, multiple regression tests using SPSS version 25 tools and the Sobel test. The results of this research are 1) celebrity endorsement has a positive effect on customer loyalty 2) brand image has a positive effect on customer loyalty 3) celebrity endorsement has a positive effect on customer satisfaction 4) brand image has a positive effect on customer satisfaction 5) customer loyalty has a positive effect on satisfaction customers 6) customer satisfaction can mediate the influence of celebrity endorsement on customer loyalty 7) customer satisfaction can mediate the influence of brand image on customer loyalty.